2021
DOI: 10.3390/cancers14010041
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Direct and Indirect EZH2 Inhibition in Rhabdomyosarcoma Cell Lines

Abstract: Enhancer of Zeste homolog 2 (EZH2) is involved in epigenetic regulation of gene transcription by catalyzing trimethylation of histone 3 at lysine 27. In rhabdomyosarcoma (RMS), increased EZH2 protein levels are associated with poor prognosis and increased metastatic potential, suggesting EZH2 as a therapeutic target. The inhibition of EZH2 can be achieved by direct inhibition which targets only the enzyme activity or by indirect inhibition which also affects activities of other methyltransferases and reduces E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 61 publications
0
0
0
Order By: Relevance
“…In FPRMS, the pro-apoptosis phenotype appeared to be driven by ATRA potentiated by EZH2 inhibition. This pro-apoptotic phenotype in FPRMS has been observed in a number of previous studies where RH30 cells treated with EZH2i resulted in a dose-dependent increase in apoptosis rather than differentiation [13,14]. This apoptotic phenotype may be immune-related as genes of the IFN-α pathway were upregulated.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…In FPRMS, the pro-apoptosis phenotype appeared to be driven by ATRA potentiated by EZH2 inhibition. This pro-apoptotic phenotype in FPRMS has been observed in a number of previous studies where RH30 cells treated with EZH2i resulted in a dose-dependent increase in apoptosis rather than differentiation [13,14]. This apoptotic phenotype may be immune-related as genes of the IFN-α pathway were upregulated.…”
Section: Discussionsupporting
confidence: 71%
“…Together these results suggest a pro-differentiative effect of EZH2 inhibition in RMS [7,14,15]. However, these single agent targeting strategies did not lead to complete differentiation or apoptosis in RMS models.…”
Section: Introductionmentioning
confidence: 79%
“…Recent research has suggested that enhancer of zeste homolog 2 (EZH2) serves as a key component of polycomb repressive complex 2 (PRC2) (12). EZH2 serves a role in chromosomal structure formation, cell cycle regulation, senescence, cell differentiation and promotion of tumor growth and metastasis in malignant tumor models (13)(14)(15). Hussein et al (16) reported a notable correlation between high EZH2 expression and TNBC phenotype, suggesting its biological role in this aggressive disease.…”
Section: Introductionmentioning
confidence: 99%
“…ATXII was found to induce DNA double-strand breaks and cell cycle S phase accumulation without directly binding to the DNA [21]. In rhabdomyosarcoma, increased EZH2 protein levels are associated with poor prognosis and increased metastatic potential [22]. Direct and indirect targeting of EZH2 showed differential efficacy due to divergent epigenetic and cellular signaling regulations in different rhabdomyosarcoma cell subtypes [22].…”
mentioning
confidence: 99%
“…In rhabdomyosarcoma, increased EZH2 protein levels are associated with poor prognosis and increased metastatic potential [22]. Direct and indirect targeting of EZH2 showed differential efficacy due to divergent epigenetic and cellular signaling regulations in different rhabdomyosarcoma cell subtypes [22]. A research study by Lavoie et al using cell surface proteomics, transcriptomics, and tissue specimens uncovers B7-H3 as a major immunoregulatory molecule expressed by rhabdomyosarcomas and not by normal human tissues [23].…”
mentioning
confidence: 99%